Poznoantična utrjena naselbina Tonovcov grad pri Kobaridu = Late Antique fortified settlement Tonovcov grad near Kobarid Naselbinski ostanki in interpretacija = Settlement remains and interpretation - Ciglenečki, Slavko (Opera Instituti Archaeologici Sloveniae, 2011)
This monograph presents the results of archaeological investigations of the Late Antique fortified hilltop settlement Tonovcov grad near Kobarid. This settlement is one of the best preserved Late Antique settlements in Slovenia and the southeastern Alpine area.In the first chapters, the geographical position and the research history are presented. Following are the overview of archaeological sites in the Soča River valley and the road network in Late Antiquity.